KCl‐induced high temperature corrosion of selected commercial alloys: Part II: alumina and silica‐formers. Issue 1 (16th July 2015) - Kiamehr, S.; Dahl, K. V.; Montgomery, M.; Somers, M. A. J.
Abstract : Laboratory testing on selected alumina and silica‐forming alloys was performed to evaluate their performance against high temperature corrosion induced by potassium chloride (KCl). The alloys studied were FeCrAlY, Kanthal APM, Nimonic 80A, 214, 153MA and HR160. Exposure was conducted at 600 °C for 168 h in flowing N2 (g)+5%O2 (g)+15%H2 O(g) (vol.%) with samples covered under KCl powder. A KCl‐free exposure was also performed for comparison. Corrosion morphology and products were studied with scanning electron microscopy (SEM), energy dispersive X‐ray spectroscopy (EDS) and X‐ray diffractometry (XRD). It was observed that alloying with aluminum did not lead to the formation of protective alumina for the studied alloys. The silicon containing stainless steel 153MA showed an analogous performance to low‐silicon austenitic stainless steels of similar chromium and nickel contents. For alloy HR160, a potassium‐chromium‐silicon‐oxygen containing layer forms as the innermost corrosion product. The layer was uniformly distributed over the surface and appears to render some protection as this alloy exhibited the best performance among the investigated alloys. To reveal further aspects of the corrosion mechanism, Nimonic 80A was exposed in static laboratory air for the same duration and temperature with either KCl or K2 CO3 deposits. Comparison of results obtained with these experiments showed that both potassium and chlorine can play a role in material degradation by KCl.